Powojenne szkolnictwo żydowskie na przykładzie Żydowskiej Szkoły Powszechnej w Dzierżoniowie w latach 1945-1950 - Grużlewska, Anna (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2020)
The article presents the establishments and development of Jewish school in Dzierżoniów, which allows an examination of the circumstances that initiated postwarJewish educational system in Polish Lower Silesia. Particular emphasis was put on descirbing the teaching staff, problems of the institution and political issues present during its functioning.
Keywords: regionalizm; region; Śląsk; Polska; Czechy; Niemcy; czasopismo regionalne; czasopismo historyczne